Examination of Post-Disaster Temporary Housing Units in the Scope of Deployment Directions - Süalp, Çetin; Coşgun, Nilay (My University, 2023)
Temporary houses are needed for the rehabilitation phase, which emerges a few weeks after the disaster and lasts until the finish of permanent houses. It is practically difficult to construct temporary houses in a short period. In particular, there are technical problems related to the logistics and installation speed. Therefore, the deployability feature, which can speed up the process, comes to the fore in this context. In this study, three examples with different deployment directions, which could be deployed in one, two and four directions, were examined regarding their capacity, storage and transportation, area per user and effective land utilization. Selected examples from the literature were compared according to the performances. As a result of this study, each example came to the fore in different performances. In this way, the advantages and disadvantages of each system were shown.
Keywords: Rehabilitation; earthquake; Disaster management; deployable structures